Música Contemporânea em Minas Gerais: os Encontros de Compositores Latino-americanos de Belo Horizonte (1986-2002) - Lovaglio, Vânia Carvalho (2010)
The aim of this work is to understand the historic process which achieved the construction of the Latin American contemporary music movement in Belo Horizonte, more specifically, the Latin American Composer s Gatherings of Belo Horizonte, held in the years 1986-1988-1992-2002 sponsored by the Fundação de Educação Artística. It was also possible to get knowledge of their artistic cultural programs (works, composers, performers) in which one can found included the production of Brazilian music and music of Minas Gerais, as well as the theoretical questions presented in form of Thematic Panels. As for their importance not only in local, but national and international levels, the Latin American Composer s Gatherings have had a strong social impact in the city of Belo Horizonte in the decades of 1980-90, mainly through the academic scene, contributing to the musical formation of young composers and performers and for the structure of the musical composition area at the Escola de Música da Universidade Federal de Minas Gerais. As far as the common problems facing Brazil and Latin America on the above decades are concerned, a changing in favor of the Latin American contemporary music passed necessarily by the understanding that the politic and economic aspects were strongly connected with the cultural one. As for their production and musical diffusion, a major participation of all professionals - composers, performers, educators and musicologists - in the sense of interfering in the current teaching musical model practiced in institutions of fundamental, median and college levels.